Tailoring the CdS surface structure for photocatalytic applications. Issue 5 (October 2020) - Kumar, S. Girish; Kavitha, R.; Nithya, P.M.
Graphical abstract: Surface modified CdS based nanomaterials for photocatalytic applications. Highlights: Surface modification of CdS to improve the performance is discussed. Scope of CdS based nanomaterials in photocatalytic reactions is reviewed. CdS-composite with various co-catalysts is highlighted. Structure-morphology driven photocatalytic activity of CdS is surmised. Abstract: Semiconductor mediated photocatalysis is envisaged as a promising approach to initiate the diverse redox reactions under the ambient conditions. Although titania still remains as benchmark photocatalyst, its wide band gap and rapid charge carrier recombination blights their utility under natural solar light. Thus, search of functional materials with narrow gap and suitable band edge potentials has drawn significant attention for photocatalytic applications. Towards this end, CdS have been impressive as prime nanomaterial which is mainly attributed to their visible light absorption capacity, more negative conduction band edge potential, and simplistic preparation with diverse morphologies and their proficiency to form stable heterostructure with variety of co-catalysts. However, photocorrosion vulnerability of CdS becomes the origin of intimidation for long term operations and massive charge carrier recombination constrains their performance. In this review article, surface structure of the CdS modified with various co-catalysts such as metal NPs, metal oxides, sulfides, phosphides, carbides, g-C3 N4, polymers and carbon materials to overcome the aforementioned drawbacks is discussed. Besides, fundamental aspects concerning the relationship between the crystal structure and morphological effects of CdS on the photocatalytic property is emphasized. The preparative methods, charge carrier dynamics and performance of CdS-based binary and ternary composites benefitting the model reactions such as pollutant degradation, hydrogen evolution and organic functional group transformation is reviewed in detail. The literature survey concludes that the surface modifications with co-catalysts can be the constructive approach for exploring the CdS based nanomaterials for broader environmental applications.